2010
DOI: 10.1007/s11418-010-0473-y
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive activity of Hypericum grandifolium Choisy in mice

Abstract: The present study investigated the antinociceptive activity of different extracts prepared from the aerial parts of blossom of Hypericum grandifolium Choisy-a species native to the Macaronesian Region-using the acetic acid-induced writhing, formalin and tail flick test in mice. Oral administration of methanol extract (500 and 1,000 mg/kg p.o.), the aqueous, butanol and chloroform fractions (500 mg/kg p.o.) as well as subfractions F2 and F3 (45 mg/kg p.o.) from the chloroform fraction significantly inhibited ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Furthermore, some Hypericum species, such H. montbretii (Can and Ozkay, ), H. perforatum , and Hypericum hircinum (Diana et al ., ), have been reported to have sedative activity in relation to the CNS. Another CNS‐related activity, centrally mediated antinociception, has been reported in rodents after administration of extracts of Hypericum grandifolium (Bonkanka et al ., ), H. caprifoliatum , Hypericum polyanthemum (Viana et al ., ), H. canariense , H. glandulosum (Rabanal et al ., ), and Hypericum reflexum (Sánchez‐Mateo et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some Hypericum species, such H. montbretii (Can and Ozkay, ), H. perforatum , and Hypericum hircinum (Diana et al ., ), have been reported to have sedative activity in relation to the CNS. Another CNS‐related activity, centrally mediated antinociception, has been reported in rodents after administration of extracts of Hypericum grandifolium (Bonkanka et al ., ), H. caprifoliatum , Hypericum polyanthemum (Viana et al ., ), H. canariense , H. glandulosum (Rabanal et al ., ), and Hypericum reflexum (Sánchez‐Mateo et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…After 5 min, each mouse was placed in a transparent observation cage, and the number of writhing events within 20 min was counted. Body writhing was defined as a contraction of the abdominal muscles together with stretching of the handsaw (Bonkanka et al, 2011).…”
Section: Acetic Acid-induced Writhing Testmentioning
confidence: 99%
“…Furthermore, some Hypericum species, such as H. hircinum and H. perfoliatum (Diana et al, 2007), have been reported to have sedative activity in relation to the CNS. Another CNS-related activity, centrally mediated antinociception, has been reported in rodents after administration of extracts of H. perforatum, H. caprifoliatum, H. polyanthemum (Viana et al, 2003), H. brasiliense (Rieli Mendes et al, 2002), H. triquetrifolium (Apaydin et al, 1999), H. empetrifolium (Trovato et al, 2001), H. reflexum (Sánchez-Mateo et al, 2006), H. canariense, H. glandulosum and H. grandifolium (Bonkanka et al, 2011).…”
Section: Introductionmentioning
confidence: 98%